Long-term outcome of Bartter syndrome in 54 patients: A multicenter study in Korea - Choi, Naye; Kim, Seong Heon; Bae, Eun Hui; Yang, Eun Mi; Lee, Keum Hwa; Lee, Sang-Ho; Lee, Joo Hoon; Ahn, Yo Han; Cheong, Hae Il; Kang, Hee Gyung; Hyun, Hye Sun; Kim, Ji Hyun (Frontiers in Medicine, 2023)
Introduction Bartter syndrome (BS) is a rare salt-wasting tubulopathy caused by mutations in genes encoding sodium, potassium, or chloride transporters of the thick ascending limb of the loop of Henle and/or the distal convoluted tubule of the kidney. BS is characterized by polyuria, failure to thrive, hypokalemia, metabolic alkalosis, hyperreninemia, and hyperaldosteronism. Potassium and/or sodium supplements, potassium-sparing diuretics, and nonsteroidal anti-inflammatory drugs can be used to treat BS. While its symptoms and initial management are relatively well known, long-term outcomes and treatments are scarce. Methods We retrospectively reviewed 54 Korean patients who were clinically or genetically diagnosed with BS from seven centers in Korea. Results All patients included in this study were clinically or genetically diagnosed with BS at a median age of 5 (range, 0–271) months, and their median follow-up was 8 (range, 0.5–27) years. Genetic diagnosis of BS was confirmed in 39 patients: 4 had SLC12A1 gene mutations, 1 had KCNJ1 gene mutations, 33 had CLCNKB gene mutations, and 1 had BSND mutation. Potassium chloride supplements and potassium-sparing diuretics were administered in 94% and 68% of patients, respectively. The mean dosage of potassium chloride supplements was 5.0 and 2.1 mEq/day/kg for patients younger and older than 18 years, respectively. Nephrocalcinosis was a common finding of BS, and it also improved with age in some patients. At the last follow-up of 8 years after the initial diagnosis, 41% had short stature (height less than 3rd percentile) and impaired kidney function was observed in six patients [chronic kidney disease (CKD) G3, n = 4; CKD G5, n = 2]. Conclusion BS patients require a large amount of potassium supplementation along with potassium-sparing agents throughout their lives, but tend to improve with age. Despite management, a significant portion of this population exhibited growth impairment, while 11% developed CKD G3–G5.